The Essence of “Merdeka Belajar” as a Transformational Culture Change in Indonesian Education - Zulfatun Ni’mah; Ari Susanto (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to review the essence of the "Merdeka Curriculum" in carrying out its role as a curriculum that transforms educational culture in Indonesia in accordance with the demands of the times in the era of "society 5.0." The research method used in this study is the library research method using a qualitative descriptive approach, where the source of the data used in this study is in the form of books or documents related to research. The primary data used in this study is the Merdeka Belajar guidebook and publications related to Merdeka Belajar delivered by the Minister of Education, Nadim Anwar Makarim, as the initiator of the Merdeka Belajar curriculum itself. Meanwhile, the secondary data in this study are books, journals, and articles with high reputation and credibility related to education and the Merdeka Belajar curriculum itself. The data collection technique used in this study is documentation; the data will be analyzed using qualitative descriptive techniques and validated using source triangulation. The findings of this study are as follows: 1) the purpose of holistic education, namely education that focuses on developing children's noble character rather than just their cognitive abilities; 2) freedom of learning mandates freedom of learning by placing students, teachers, and principals in a school institution as the main figures in the teaching and learning process; and 3) independent learning provides flexibility to schools in order to improve the quality of student learning through education.